Evaluating the Performance Diagnostic Checklist‐Human Services to assess incorrect error‐correction procedures by preschool paraprofessionals. Issue 1 (14th December 2017) - Bowe, Melissa; Sellers, Tyra P.
Abstract : The Performance Diagnostic Checklist‐Human Services (PDC‐HS) has been used to assess variables contributing to undesirable staff performance. In this study, three preschool teachers completed the PDC‐HS to identify the factors contributing to four paraprofessionals' inaccurate implementation of error‐correction procedures during discrete trial training sessions. The PDC‐HS indicated insufficient training as a contributing factor. We then implemented a nonindicated intervention (posting reminders), followed by an indicated intervention (behavioral skills training). The nonindicated intervention failed to produce desired performance improvements; however, the PDC‐HS indicated intervention resulted in improvements for all paraprofessionals.